Immunisation and the Law: Slippery Slope to a Healthy Society - Kerr, Jessica (Victoria University of Wellington Law Review, 2006)
The immunisation of children against communicable diseases is a crucial public health intervention. Yet the understandable prioritisation of parental autonomy within New Zealand immunisation policy has contributed to consistently unsatisfactory coverage rates, in both absolute and comparative terms. If our immunisation law could be strengthened to eliminate ‘passive’ non-immunisation without fatally undermining parental choice, the goals of ‘population immunity’ might be achievable. Of the three reform options explored by this paper, two are rejected as unworkable. The first, a universal mandatory immunisation requirement, might be justifiable in principle but would encounter prohibitive public opposition. The second, an ‘informed choice’ requirement limited to beneficiaries, is unprincipled and potentially ineffective. The recommended option is more moderate and equitable. Creating a presumption in favour of immunisation at the point of school-entry would shift the legal focus from ‘informed consent’ to United States-style ‘informed refusal’. The degree of effort required to invoke a statutory exemption to immunisation would depend upon the extent to which policy-makers were satisfied that only parents implacably and legitimately opposed to immunisation were invoking it. Barring a dramatic increase in the size of the anti-immunisation lobby, it is suggested that an informed refusal requirement could successfully eliminate passive non-immunisation, thereby potentially achieving population immunity while substantially preserving parental autonomy.